Layer-dependent temperature evolution and cooling kinetics in non-isothermal Powder Bed Fusion of polypropylene - Schlicht, Samuel; Drummer, Dietmar (Procedia CIRP, 2024)
Non-isothermal laser-based powder bed fusion of polymers (PBF-LB/P) allows for the support-free additive manufacturing of semi-crystalline polymers at room temperature. The present paper demonstrates the support-free manufacturing of polypropylene, enabled through discretized exposure strategies, constituting fundamentally different processing conditions compared to quasi-isothermal PBF-LB/P at elevated temperatures. By applying fractal, superposed exposure strategies, the stable processing across a large geometric range is demonstrated. Thermographic in situ investigations show a negative correlation of the number of layers and emerging peak temperatures, contrasting the thermal evolution in quasi-isothermal PBF-LB/P. Complementary, post-coating equilibrium temperatures display a negative correlation with the geometry-dependent surface-volume ratio, inducing the emergence of geometry-dependent morphological characteristics while implicitly adapting thermal boundary conditions for subsequent layers. The overheating of initial layers alongside geometry-dependent heat accumulation implies the dynamic adaption of the applied energy density in non-isothermal, support-free PBF-LB/P, compensating for layer- and geometry-induced locally insufficient heat dissipation.
Keywords: Powder bed fusion; non-isothermal; laser sintering; support-free; polypropylene; low temperature